Analysis of the salmon fishing season of 2022 - S. L. Marchenko (Известия ТИНРО, 2023)
Pacific salmon fishery in the Far East of Russia in 2022 is analyzed. The reasons for discrepancy between forecasted and actual landing of pacific salmon are discussed. Measures to improve the management and scientific support of the pacific salmon fishery are proposed.